Bullseye - Patterson, James, 1947-; Ledwidge, Michael (Patterson, James, 1947- Detective Michael Bennett thriller, 2016)
Snow blankets the avenues of Manhattan's exclusive Upper West Side. The storm is the perfect cover for a fashionable, highly trained team of lethal assassins as they prowl the streets, hunting their prey. But their first hit is simply target practice. Their next mission may very well turn the Cold War red-hot once again. Stepping directly into the line of fire, the president of the United States is in New York for a summit at the United Nations with his Russian counterpart. Pulled away from his family and pressed into service, Detective Michael Bennett must trace the source of a threat that could rip the country apart-- and ignite a war the likes of which the world has never seen. With allegiances constantly in doubt and no one above suspicion, only Bennett can save the president-- and the country-- before the assassins' deadly kill shot hits its mark.